CK‐18 cell death markers improve the prediction of histological remission in autoimmune hepatitis during biochemical remission. (29th December 2020) - Derben, Finn C.; Engel, Bastian; Zachou, Kalliopi; Hartl, Johannes; Hartleben, Björn; Bantel, Heike; Schramm, Christoph; Dalekos, George N.; Manns, Michael P.; Jaeckel, Elmar; Taubert, Richard
Abstract: Incomplete histological remission of autoimmune hepatitis (AIH) is associated with a reduced long‐term survival and an increased relapse rate even during biochemical remission (BR). The aim of this international multicentre study was to explore the diagnostic fidelity of cytokeratin‐18 cell death markers to noninvasively detect incomplete histological remission. Thereby, cytokeratin‐18 cell death marker M65 but not ALT and immunoglobulins was significantly higher in patients with incomplete histological remission (mHAI ≥ 4) compared to those with mHAI ≤ 3. M65 levels > 305 U/L, identified in the training cohort, facilitated the noninvasive detection of incomplete histological remission with a sensitivity of 75% and negative predictive value of 86% in the validation cohort. While BR with M65 < 305 U/L suggested complete histological remission (86%), BR with M65 > 305 U/L reduced the rate of histological remission to 60%. In conclusion, M65 may help to better select patients for or to reduce surveillance liver biopsies in the future.